RESISTENSI PEDAGANG PASAR DALAM PROYEK REVITALISASI PASAR KOLOMBO - , FITRIANA NURCAHYANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Revitalization market persist, although not the final price with the merchants must be willing to be relocated to a new place that is not worthy. There are many merchants who have not gotten the market stall or los in Kolombo market. Kolombo market traders complained many losses after relocating to a temporary place. The purpose of this study is to determine how resistance traders in Kolombo market revitalization project. This research uses descriptive qualitative method. The process of data collection is through interviews, observation, and documentation. The Researcher conducted a theoretical review. In the first theoretical review, the researcher stated in theory Aggressiveness a motive to commit the response to abuse, humiliation and frustration with the intent and purpose to hurt and harm others. In the second theoretical review, the researcher stated that the form of resistance is very diverse and can be viewed as a form of disobedience, a rejection of unwelcome conditions. In the third theoretical review, the researcher stated relative deprivation a gap between what the trader to and what the traders in Kolombo market revitalization project. The push factors that traders doing resistance is solidarity economics traders factors. Resistance carried traders who do have an impact on the economy. In addition, the resistance did the traders have the meaning of solidarity and welfare. Results of this study showed resistance to Kolombo market traders actually do not fully want to break the rules that apply, but there are factors of dissatisfaction with government policy and the other villages had its own reasons for reasons primarily economic factors. Analysis of the resulting form of village government and the Government of Sleman district to better accommodate aspiration traders through Paguyuban Pedagang Pasar Kolombo (P3K) by approaching the form of intensified public discussion to reach agreement more transparent pricing and more aspiring traders hope to fulfill the rights of temporary relocation site are more satisfy.